ESTABLISHING A WEB PORTAL FOR ADVICE ON HUMAN TALENT FOR SMES OF THE DIDACTIC COMPANY AGH SAS - Arévalo Hernández, Franklin Giovanni
Due to the constant changes in technologies and innovation that the 21st century presents, being at the forefront of these is a must, seeking to be at the level of organizations that have an advanced technological system and that is why the process of human talent is being reinforced digitally, since its stability ensures a better development in the organization and a clearer order of everything it may contain. For that reason each one of the procedures carried out in the macro process of human talent is being handled in a digital way. The AGH SAS didactic company of the Administrative Management Center SENA DC, which constantly needs to be in communication with the SMEs it is supporting, implemented a platform where communication with the managers of these organizations is more feasible and concise, since it facilitates the relationship with the client and if an extra communication is required, this is done through this tool; for this, pilot tests and surveys were carried out, evidencing the collision that caused immediate communication with the client, thus making the process more effective. Then data tabulation was carried out showing the great percentage of approval that this method of communication could have, finally the impact that it has generated in the organizations advised was measured through a survey applied to the supported businessmen.